Mental Health Awarness: The Role of Media - Abhijit, Pathak (International Journal of Psychosocial Rehabilitation, 2020)
Mental Health is a vital concern across the globe and it thrives on physical, social, and economic well- being in continuum. Awareness of it itself play a role in maintaining mental health. Mental health awareness has dual aspect; first, self awareness of mental well- being which helps a person to avoid those social, economic, and cultural environment which results in behavioral adversities to health; especially mental health. The second aspect is more positive in nature and constructs positive perspective among people and develops empathy towards a person suffering from mental illness and thus, prevents their ostracisation. Media’s potential is not confined to urban centers and small towns. Rural mass can be informed and made aware which can improve their over all mental health literacy. Mental Health messages through different forms of media can act as tool for understanding psychopathology and for advocating mental health.